Pregnancy Outcome of Mothers who Used Smokeless Tobacco for Five Years or More (Bangladesh Journal of Child Health, 2012)
Background: Approximately 39% women in Bangladesh use smokeless tobacco (ST). The incidence of adverse pregnancy outcomes like spontaneous abortion, stillbirth, preterm birth and delivery of low birth weight baby (LBW) are quite high in our country. Objective: To determine the frequency of spontaneous abortion, stillbirth, delivery of preterm & LBW baby of mothers who used ST for prolonged period. Methodology: This retrospective cohort study was carried out in the Department of Paediatrics and Department of Obstetrics & Gynecology, MAG Osmani Medical College Hospital, Sylhet, between July 2007 and June 2009. A total of 150 mothers using ST for 5 years or more & their recently delivered newborn infants (mother-neonate pair) satisfying the selection criteria were enrolled as cases by purposive sampling. 150 suitably matched mother-neonate pairs were enrolled as controls. Detailed history of each mother about the outcome of recent and previous pregnancy/ pregnancies within the last 5 years was taken meticulously. Physical examination of the mother was done thoroughly. Each newborn was assessed for birth weight and gestational age. Results: Baseline characteristics of cases and controls were comparable. Use of ST for > 5 years was significantly associated with spontaneous abortion (P < 0.01) and carried a risk of having spontaneous abortion 2.3 times more than that of non-ST users. It was also significantly associated with stillbirth (P < 0.01) and carried a risk of having stillbirth 2 times higher than that of non-ST users. Use of ST for > 5 years was significantly associated with preterm delivery (P < 0.001) and carried a risk of having preterm delivery 3.1 times more than that of non-ST users. It was also significantly associated with delivery of LBW baby (P < 0.001) and carried a risk of having delivery of LBW baby 4.1 times higher than that of non-ST users. Conclusion: Frequency of spontaneous abortion, stillbirth, preterm delivery & delivery of LBW babies were much higher among mothers who used ST for about 7½ years. Women of child bearing age should be discouraged to use ST. DOI: http://dx.doi.org/10.3329/bjch.v35i1.10366 BJCH 2011; 35(1): 6-10